The history of written cultures matters - Bouza Álvarez, Fernando (2023)
Books and writing have a history that is inseparable from their various forms and the materials in which they are or were produced.  They are also closely associated with the evolution of administrative procedures and ways of ruling, the emergence of public  opinions and influential political oppositions, or even the involvement of citizens in civic and critical activity. This mutation and search for expressive practices and places of knowledge is a constant feature of the cultures of books, writing and reading and is very  relevant nowadays. Today, these transformations also involve digital devices in written communication and book production, and  their relationship in a more complex book system, not a mere paradigm shift. Readers, authors, and producers are required to have new skills and adapt to the ways in which they experience written communication, changes that can be understood in the light of  other major changes that have already taken place in the contexts of the various forms of manuscript and mechanical printing.